Depression impacts the course of recovery in patients with acute low-back pain - Melloh, Markus; Elfering, A.; Käser, A.; Salathé, C.; Barz, T.; Aghayev, E.; Röder, C.; Theis, J. (2013)
Little is known about the course of recovery of acute low back pain (LBP) patients as a function of depression. In a prospective study, 286 acute LBP patients were assessed at baseline and followed up over 6 months. Recovery was defined as improvement in the Oswestry Disability Index (ODI). Repeated-measures analysis of covariance was employed with ODI as repeated factor, age, sex, and body mass index as covariates, depression and all other potential prognostic factors as between-subject factors. Of study participants, 18% were classified as depressive (>33 points on the Zung Self-Rating Depression Scale). Of 286 participants, 135 were lost to follow-up. In the longitudinal sample of 151 patients the course of recovery was slower in depressive patients. Depression was associated with LBP especially after 6 weeks and should therefore be included in screening instruments for acute LBP patients to identify those at risk of delayed recovery at an early stage. © 2013 Taylor and Francis Group, LLC.